ENVIRONMENTAL PROTECTION AND ECONOMIC GROWTH - Teles, Vladimir Kuhl; Arraes, Ronaldo (Análise Econômica, 2019)
This paper explores the link between environmental policy and economic growth by employing an extension of the AK Growth Model. We include a state equation for renewable natural resources. We assume that the change in environmental regulations induces costs and that economic agents also derive some utility from capital stock accumulation vis-a-vis the environment. Using the Hopf bifurcation theorem, we show that cyclical environmental policy strategies are optimal, providing theoretical support for the Environmental Kuznets Curve.